Effects of thermal annealing on the morphology and structural characteristics of zinc oxide nanopowders for triboelectric nanogenerator applications - Mamat, Mohamad Hafiz; Kamaruzaman, Dayana; Kamal Ariffin, Nurul Izzati; A Subki, A Shamsul Rahimi; Abdullah, Mohd Hanapiah; Parimon, Norfarariyanti; Yaakob, Muhamad Kamil; Malek, Mohd Firdaus; Shameem Banu, Itreesh Basha; Vasimalai, Nagamalai; Abu Bakar, Suriani; Mohamed, Azmi; et al. (Penerbit Akademia Baru, 2022)
The influence of thermal annealing on the surface morphologies and structural characteristics of zinc oxide (ZnO) nanopowders synthesized via the solution immersion method for triboelectric nanogenerator applications is reported in this paper. The ZnO nanopowders were thermally treated at different temperatures of annealing in the ranges between 300C to 700C for 1 hour, and their surface morphologies and structural properties were studied using field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analysis. The ZnO nanopowders have a polycrystalline, hexagonal wurtzite structure and are composed of ZnO nanoparticles and hexagonal nanorods. ZnO based tribolectric nanogenerators were fabricated with these nanopowders and their performance was assessed in terms of the output voltage. It is found that the ZnO based triboelectric nanogenerator fabricated with ZnO crystallinity of ZnO nanopowders, which in turn, influences the output voltage of ZnOnanopowders annealed at 500C has superior performance compared with the other nanogenerators, with an average output voltage of 1.95 V. This corresponds to a fourfold increase in output voltage relative to that of the ZnO based triboelectric nanogenerator fabricated with as-deposited ZnO nanopowders. In conclusion, thermal annealing significantly influences particle size and crystallinity of ZnO nanopowders, which in turn, influences the output voltage of ZnO based triboelectric nanogenerators.